Modification AES with Permutation from DES (Journal of the College of Basic Education, 2023)
The Advanced Encryption Standard (AES) encryption algorithm is a block cipher that uses an encryption key and a several rounds of encryption. A block cipher is an encryption algorithm that works on a single block of data at a time. In the case of standard AES encryption the block is 128 bits, or 16 bytes, in length. The term “rounds” refers to the way in which the encryption algorithm mixes the data re-encrypting it ten to fourteen times depending on the length of the key[1]. The AES algorithm itself is not a computer program or computer source code. It is a mathematical description of a process of obscuring data. A number of people have created source code implementations of AES encryption, including the original authors.This paper we introduces a modification study for the AES with new permutation of portion. We add initial permutation to beginning of AES encryption and when decrypt add permutation inverse to its end. These make it more confusion then original AES.